Effect of acyl donor chain length on isoquercitrin acylation and biological activities of corresponding esters - Hadj Salem, J.; Humeau, C.; Chevalot, I.; Harscoat, C.; Vanderesse, R.; Blanchard, Fabian; Fick, M. (Process Biochemistry, 2010)
International audience The enzymatic acylation of isoquercitrin with fatty acid esters of various carbon chain lengths was carried out in 2-methyl-2-butanol using Novozym 435®. The conversion yield and the initial rate decreased from 66% to 38% and from 17.7 to 10.1 μmol/h respectively, as the carbon chain of the acyl donor increased from C4 to C18. Isoquercitrin acylated derivatives showed higher xanthine oxidase inhibition activities than isoquercitrin. This property increased with the lipophilicity of the derivative esters. The scavenging activity of isoquercitrin esters against ABTS and DPPH radicals decreased with the acyl chain length. Conversely, for esters from C6 to C18, a linear growing relationship can be established between the chain length and the superoxide radical scavenging activity. Furthermore, an improved antiproliferative effect on Caco2 cancer cells was induced by addition of isoquercitrin esters comparing with isoquercitrin.